Анализа на институционалната поддршка на одржливи практики во претпријатијата во Република Северна Македонија во функција на поттикнување на одржлив развој - Трајков, Жарко (Економски факултет, УКИМ, Скопје, 2021)
The doctoral dissertation focuses on the impact of institutional support on developing and implementing sustainable business practices in the Republic of North Macedonia. The research subject is the world experience and the global perspective, with a review of the essential aspects of sustainable development from the historical beginnings through the circular economy to the indicators of sustainable practices and their financing sources. The research itself includes companies, organizations, and institutions from the Republic of North Macedonia, which, with the help of empirical research, established sustainable practices in crucial segments of sustainable development. The components management, clients, community, employees, environment, financial and non-financial institutional support are covered. The analyses performed are using Pearson's linear correlation coefficient and comparative studies. The connection of the various factors in realizing sustainable practices in enterprises is fascinating. The fact is that one-off interventions are insufficient, without the possibility to contribute to the propulsion of organizations. Setting clear goals by defining the vision, mission and underlying ideology, using instrumental values as connective tissue, is inevitable in today's way of functioning. In that way, this is a more common practice, not a distinctive advantage of organizations. All this is in the function of creating conditions for the survival and sustainability of organizations. The situation is much more complex for SMEs, socially responsible firms, green businesses, and social enterprises. It is necessary to look at the overall condition to fulfill these goals, i.e., the big picture, through holism in the approach.
Analysis of institutional support on sustainability in the Republic of Northern Macedonia firms in the function of promoting sustainable development
Докторска дисертација одбранета во 2021 година на Економскиот факултет во Скопје, под менторство на проф. д–р Стојан Дебарлиев.
Keywords: sustainable development, sustainable practices, organizations, institutional support, Republic of North Macedonia